HETEROGENEITY IN HABITAT USE OF THREE THREATENED FRESHWATER CATFISHES (SILURIDAE: SILURIFORMES) IN FIVE MAJOR TROPICAL RIVERS OF INDIA - Dr. Shailendra Kumar Singh, (International Journal of Innovations in Engineering Research and Technology, 2014)
Ompok panda, O. pabo, and O. bimaculatus were sampled from 40 different locations in the Tone, Gomti, Ganga, Bramhaputra, and Hoogly rivers to determine the most important habitats for these endangered catfish. It was determined that environmental circumstances impact species occurrences and assemblage traits via the use of canonical correspondence analysis. An analysis of the microhabitat, hydro morphological factors, depth, and velocity, followed by conductivity; temperature; TDS was shown to be crucial in structuring the three catfish species. It has been shown that the presence of O. panda in rivers with swift current and shallow depth is substantially related to the presence of O. bimaculatus, which prefers a slower current and greater depth. Other environmental factors, including conductivity, TDS, and pH, were also shown to influence the Ompok species' habitat preferences. Environmental factors have a significant impact on the Ompok species, and our findings demonstrate the need for their protection and management.